Morphological description of early zoeal stages of the snapping shrimp Alpheus buckupi (Caridea: Alpheidae) reared in the laboratory - Pescinelli, Régis Augusto [UNESP]; Sanches, Nádia de Moraes [UNESP]; Costa, Rogerio Caetano [UNESP] (Wiley, 2022)
Larval information plays an important role in life history and population dynamics studies, as well as in phylogenetic and systematic ones. The early zoeal stages (zoea I, II and III) of the snapping shrimp Alpheus buckupi were described and illustrated based on laboratory-hatched larvae from parental females sampled in Cananéia, São Paulo State, Brazil. The morphological characters of the species were compared with descriptions of other Alpheus species with a known first zoeal stage. The first zoeal stage of this species can be separated from the first zoeal stage described for the other 26 species using the following combination of characteristics: basial endite of maxillule with 2 stout spines (distal one with two rows of spinules) and 2 small plumose setae; basial endite of maxilla bilobed, with 3 and 4 simple setae on proximal and distal lobe, respectively, and five (3 strong and 2 slender) simple setae arranged (2 + 2 + 1) on the basis of first maxilliped. The substantial progress in larval knowledge is fundamental to areas such as ecology and will allow us to better understand the distribution of different early life stages of Alpheus species in the meroplankton community.
Keywords: Decapoda; intertidal; larval development; snapping shrimp